Alat Vital Sign Portable Dengan Parameter SpO2 Dan Heart Rate Dilengkapi Layar TFT Berbasis ESP32 - Henra Jasman; Anita; Samsuar (MEDIKA TRADA, 2025)
Portable vital sign devices with SpO2 (oxygen saturation in the blood) and heart rate parameters are designed to be portable devices that are easy to operate by users and can provide accurate monitoring results. This device uses SpO2 and heart rate sensors integrated with the ESP32 microcontroller, where the data reading results are displayed directly on the TFT screen. The measurement results from the device show that the average SpO2 value measured by this device has a difference of 0.4% with an average accuracy of 99.6% compared to the results of the standard device. The Heart Rate value has a difference of 3.2 BPM (beats per minute) with an average accuracy of 97.56% compared to the standard device. This shows that the device can be trusted to provide accurate vital data for users. With these advantages, the ESP32-based Vital Sign Monitor device is expected to be an efficient and economical solution for health monitoring in various environments, including homes and health facilities with limited resources